Assessment of NPP VIIRS Albedo Over Heterogeneous Crop Land in Northern China. Issue 24 (20th December 2017) - Wu, Xiaodan; Wen, Jianguang; Xiao, Qing; Yu, Yunyue; You, Dongqin; Hueni, Andreas
Abstract: In this paper, the accuracy of Suomi National Polar‐orbiting Partnership Visible Infrared Imaging Radiometer Suite (VIIRS) land surface albedo, which is derived from the direct estimation algorithm, was assessed using ground‐based albedo observations from a wireless sensor network over a heterogeneous cropland in the Huailai station, northern China. Data from six nodes spanning 2013–2014 over vegetation, bare soil, and mixed terrain surfaces were utilized to provide ground reference at VIIRS pixel scale. The performance of VIIRS albedo was also compared with Global LAnd Surface Satellite (GLASS) and Moderate Resolution Imaging Spectroradiometer (MODIS) albedos (Collection 5 and 6). The results indicate that the current granular VIIRS albedo has a high accuracy with a root‐mean‐square error of 0.02 for typical land covers. They are significantly correlated with ground references indicated by a correlation coefficient ( R ) of 0.73. The VIIRS albedo shows distinct advantages to GLASS and MODIS albedos over bare soil and mixed‐cover surfaces, while it is inferior to the other two products over vegetated surfaces. Furthermore, its time continuity and the ability to capture the abrupt change of surface albedo are better than that of GLASS and MODIS albedo. Key Points: The accuracy of the latest albedo products, including VIIRS, GLASS, and MODIS (Collection 6) over heterogeneous surfaces, was evaluated and compared Ground‐observed albedo from a wireless sensor network and an upscaling strategy specified for validation of VIIRS albedo were combined to derive ground references at pixel scale The VIIRS albedo has a high accuracy with a RMSE of 0.02 versus ground reference and successfully captures the rapid change of albedo by improving temporal resolution to daily